Impact of commonly used drugs on the composition and metabolic function of the gut microbiota - Arnau Vich Vila (Nature Portfolio, 2020)
Here, via a metagenomics analysis of population-based and disease cohorts, Vich Vila et al. study the impact of 41 commonly used medications on the taxonomic structures, metabolic potential and resistome of the gut microbiome, underscoring the importance of correcting for multiple drug use in microbiome studies.